POLITENESS STRATEGIES USED BY TEACHER AND STUDENTS IN THE ENGLISH FOREIGN LANGUAGE (EFL) CLASSROOM - Vivi Novalia Sitinjak; Dona Chrystina Situngkir; Imanuela Elpride; Priety Cecilia; Sri Melawati Hutasoit (LPSDI Bina Patria, 2023)
The aim of this research is to describe that many studies have employed politeness techniques as their main focus since Brown and Levinson first proposed it in 1987. Some of these are considered to be a formal class within an academic subject. Politeness tooimprove learning by creating a dynamic atmosphere and pleasanttinteraction between teachersaand students during the teaching and learninggprocess. Additionally, because of the relaxed atmosphere and positive interactions present, it helps inspire students to learn. The purposeoof this paper is to examine how politeness strategiesiareiusediby students and teacher during interactions in EFL classrooms. It is based on the fouritypes of politeness strategiesiproposed by Brownand Levinson (1987): bald-on-record, off-record, positive-politeness, and negative-politeness. The method employed is qualitative descriptive with literature study methodology. The researchers discovered that teacher and students employed a variety of politeness-strategy in EFLcclassroom interaction